2017
DOI: 10.21873/invivo.11124
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting the Overall Survival of Patients Irradiated for Invasive Carcinoma of the Urinary Bladder

Abstract: Abstract. Background A considerable number of patients with carcinoma of the urinary bladder are treated with an organ-preserving approach, mostly consisting of transurethral resection of the bladder tumour (TURBT) followed by irradiation with or without concurrent chemotherapy (1-3). Since many of these patients present with significant comorbidities, a personalised treatment program is often required. Such a program should ideally consider several patient-related factors, including the patient's social situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Many patients with cancer of the urinary bladder receive local or loco-regional radiotherapy with or without concurrent chemotherapy as part of a bladder-preserving multimodal treatment (12)(13)(14)(15)(16)(17). Anticipation of radiochemotherapy or radiotherapy can be associated with sleep disturbances as a consequence of emotional distress and fears.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with cancer of the urinary bladder receive local or loco-regional radiotherapy with or without concurrent chemotherapy as part of a bladder-preserving multimodal treatment (12)(13)(14)(15)(16)(17). Anticipation of radiochemotherapy or radiotherapy can be associated with sleep disturbances as a consequence of emotional distress and fears.…”
Section: Discussionmentioning
confidence: 99%
“…The KPS represents an important prognostic factor for OS and PFS in several types of cancer [ 20 , 63 , 64 , 65 ]. In our cohort, all patients with a KPS ≤ 70% died in less than six months.…”
Section: Discussionmentioning
confidence: 99%
“…A pre-radiotherapy (pre-RT) history of smoking, namely the number of pack years, was reported by several authors to be associated with worse outcomes including decreased local control (LC) and overall survival (OS) (4)(5)(6)(7)(8). Moreover, a negative impact of a greater number of pack years on treatment outcomes were also reported for patients irradiated for lung cancer or carcinoma of the urinary bladder (9)(10)(11). However, in a population-based study of 316 patients with larynx cancer, no significant associations were found between pre-RT history of smoking and outcomes in terms of disease-free survival (DFS) and OS (12).…”
mentioning
confidence: 99%